Monitoring and Evaluation of the Implementation of Public Information Disclosure Through @probolinggoimpressive Account by Probolinggo City Government - Lailatul Fitria, Nurul Jannah (Journal of Governance and Public Affairs, 2024)
The government in running the government bureaucracy is required to implement information disclosure. Public information disclosure is implemented by using websites and social media. Including the Probolinggo City Government using Instagram social media in disseminating information. This is interesting to study in order to understand the model of use and evaluation monitoring on the @probolinggoimpressive social media account by the Probolinggo City Government. The research applied a descriptive qualitative method with a case study approach in Probolinggo City in using social media. Primary data collection by interviewing competent sources; observation on the @probolinggoimpressive account; and documentation related to the research subject. The results of the study explain the concept of using Instagram @probolinggoimpressive social media in public information disclosure by the Probolinggo City Government with the concept of posting photos on the Instagram feed, publishing videos on the Instagram feed, and there are posts in the form of detailed and complete narratives, as well as posting data and information on Instagram stories, and using the live streaming feature on Instagram accounts. The concept of information disclosure is not only conveying information, but there is interaction with the public and institutions or officialdom through post comments and direct messenger. As well as tagging and sharing post features. While monitoring the evaluation of the use of Instagram social media @probolinggoimpressive in public information disclosure by the Probolinggo City Government can be seen in the monitoring and evaluation indicators on the @probolinggoimpressive account, including the Probolinggo City Government using facilities and infrastructure, information quality, type of information, organizational commitment, innovation and strategy, and digitalization